2017
DOI: 10.1007/s10964-017-0661-0
|View full text |Cite
|
Sign up to set email alerts
|

Aspirations, Expectations and Delinquency: The Moderating Effect of Impulse Control

Abstract: Although prior research finds a robust link between delinquent behavior and expectations, or an adolescent's perceived likelihood of obtaining one's future goals, fewer studies have evaluated aspirations, or the perceived importance of achieving one's goals. In addition, few studies consider how individual traits such as impulsivity affect the degree to which expectations and aspirations motivate or deter delinquent behavior. We contribute to this body of research by evaluating the independent effects of expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 47 publications
0
26
2
Order By: Relevance
“…Moreover, we were able to simultaneously test these two related yet distinct risk factors as well as test the interaction between the two predictors. Impulse control and future expectations represent distinct aspects of psychosocial development (Mahler et al, 2017;Nagin & Pogarsky, 2004), and although the current study did not find a significant interaction between the two, future research should continue to consider the relation between these variables among additional samples of developing adolescents.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Moreover, we were able to simultaneously test these two related yet distinct risk factors as well as test the interaction between the two predictors. Impulse control and future expectations represent distinct aspects of psychosocial development (Mahler et al, 2017;Nagin & Pogarsky, 2004), and although the current study did not find a significant interaction between the two, future research should continue to consider the relation between these variables among additional samples of developing adolescents.…”
Section: Discussioncontrasting
confidence: 74%
“…Two past studies found that positive future expectations were protective against delinquent behaviors for youth lacking impulse control (Chen & Vazsonyi, ; Clinkinbeard, ). A separate analysis, using the same sample as the current investigation, found no significant interaction between future expectations and impulse control in predicting self‐reported offending (Mahler et al., ). To our knowledge, prior research has yet to consider whether future expectations and impulse control interact to influence adolescent sexual behavior.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Moreover, positive expectations regarding change has been associated with better performance in terms of re-offending (Doekhie, Dirkzwager, & Nieuwbeerta, 2017;Iselin, Mulvey, Loughran, Chung, & Schubert, 2012;Mahler, Simmons, Frick, Steinberg, & Cauffman, 2017). For example, Mahler and colleagues (2017) analysed 1,216 male juvenile offenders on IQ, expectations-using the Perceptions of Opportunities Measure-and impulse control relating to self-reported offending behaviour at three points after their first official encounter with the justice system.…”
Section: Expectations Of Changementioning
confidence: 99%
“…Conversely, aspirations have been operationalized in two ways: the first captures what a parent wishes or desires his or her child to achieve despite what may be realistic or feasible (Goldenberg, Gallimore, Reese, & Garnier, 2001). A second indicator of aspirations includes the perceived importance of a future goal, but to the best of our knowledge, this has only been used to measure adolescent aspirations (Iselin, Mulvey, Loughran, Chung, & Schubert, 2012;Knight, Ellis, Roark, Henry, & Huizinga, 2017;Mahler, Simmons, Frick, Steinberg, & Cauffman, 2017). Eccles (1983) expectancy-value model also recognizes the combined role of perceived expectations for success and the perceived importance of a task in predicting achievement-related behaviors.…”
Section: Parental Expectations Aspirations and Adolescent Behaviormentioning
confidence: 99%